Morphology dependent electrocatalytic properties of hydrothermally synthesized cobalt oxide nanostructures. Issue 10 (December 2015) - Shahid, Muhammad Mehmood; Rameshkumar, Perumal; Huang, Nay Ming
Abstract: Cobalt oxide (Co3 O4 ) nanostructures with different morphologies (nanocubes, nanowires, nanobundles, nanoplates, and nanoflowers) were synthesized using a simple hydrothermal process and the electrochemical reduction of 4-nitrophenol (4-NP) was chosen as a model system to study the electrocatalytic properties of the Co3 O4 nanostructures. The nanostructures were successfully characterized using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Raman analysis. Further, glassy carbon (GC) electrodes modified with Co3 O4 nanostructures with different morphologies were characterized using electrochemical impedance spectroscopy (EIS), and the results showed the lowest charge transfer resistance ( R ct ) value for the Co3 O4 nanocubes toward the [Fe(CN)6 ] 3−/4− redox couple among all the modified electrodes. The electrochemical reduction of 4-nitrophenol (4-NP) was performed using the different Co3 O4 nanostructure modified electrodes with phosphate buffer solution (PBS) (pH 7), and it was found that the Co3 O4 nanocube modified electrode displayed a better catalytic current response. Moreover, the electrochemical detection of 4-NP at the lowest concentration levels was studied with the nanocube modified electrode using square wave voltammetry (SWV). A linear relationship was observed between the current response and the concentration ( R 2 =0.997), and the limit of detection was found to be 0.93 µM. The Co3 O4 nanocubes could reproduce the current responses in repeated experiments for the detection of 4-NP.